2016
DOI: 10.1080/1354750x.2016.1201538
|View full text |Cite
|
Sign up to set email alerts
|

Bile: miRNA pattern and protein-based biomarkers may predict acute cellular rejection after liver transplantation

Abstract: Analysis of secretome and miRNA in bile could improve our understanding of the local inflammatory process during rejection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…Schmuck et al (27) CD44, CXCL19 ELISA -/45 ACR miR-122, miR-133a, miR-148a, and miR-194 qPCR Kim et al (28) APN Proteomics -/9 ACR Adams et al (29) ICAM1 ELISA -/61 ACR Adams et al (30) IL2R Unknown -/18 ACR Tono et al (31) IL6 ELISA 11/-ACR Umeshita et al (32) IL6 ELISA -/51 ACR Morimoto et al (33) CXCL10 ELISA -/41 ACR Ericzon et al (34) Bile acids ELISA -/10 Graft function CA/CDCA ratio HPLC Buis et al (35) Bile phospholipid/bile salt ratio ELISA, spectrophotometry -/111 NAS Chen et al (36) Bile salt/phospholipid ratio ELISA 90/-Bile duct injury/NAS Geuken et al (37) Bile salt/phospholipid ratio ELISA -/28 NAS ALP Spectrophotometry…”
Section: Rt-qpcrmentioning
confidence: 99%
See 2 more Smart Citations
“…Schmuck et al (27) CD44, CXCL19 ELISA -/45 ACR miR-122, miR-133a, miR-148a, and miR-194 qPCR Kim et al (28) APN Proteomics -/9 ACR Adams et al (29) ICAM1 ELISA -/61 ACR Adams et al (30) IL2R Unknown -/18 ACR Tono et al (31) IL6 ELISA 11/-ACR Umeshita et al (32) IL6 ELISA -/51 ACR Morimoto et al (33) CXCL10 ELISA -/41 ACR Ericzon et al (34) Bile acids ELISA -/10 Graft function CA/CDCA ratio HPLC Buis et al (35) Bile phospholipid/bile salt ratio ELISA, spectrophotometry -/111 NAS Chen et al (36) Bile salt/phospholipid ratio ELISA 90/-Bile duct injury/NAS Geuken et al (37) Bile salt/phospholipid ratio ELISA -/28 NAS ALP Spectrophotometry…”
Section: Rt-qpcrmentioning
confidence: 99%
“…At the time of donor procurement ↑ PC Identify steatotic grafts (41) ↓ Choleretic activity Identify suboptimal grafts (10) ↓ CA/CDCA ratio Identify suboptimal grafts (34) During NMP HCO − 3 >18 mmol/L, pH >7.48, glucose <16 mmol/L, bile/perfusate glucose ratio <0.67, and LDH concentration <3689 U/L Predict low histological degree of bile duct injury (2) Bile production >10 mL and pH >7.45 Predict bile duct viability (14) pH <7.85 Predict NAS (16) pH <7.4 Predict NAS (53) After transplantation ↓ Na + and ↑ bile glucose-blood glucose Predict NAS (12) ↓↓↓ Lipids Identify PNF (24) ↑ CDmiR Predict ACR (26) ↑ miR-133a, miR-148a, and miR-194 Predict ACR (27,31,46,49,50) ↑ IL2, IL6, and IL8 Predict ACR (30)(31)(32) ↑ CXCL9/10 Predict ACR (27,33) ↓ Bile salt, phospholipids, and cholesterol during the first week after LT Predict NAS (35) ↑ Bile salt/phospholipid ratio during the first week after LT Predict histologically severe bile duct injury (37) ↑ miR-517a, miR-106a, and miR-892a…”
Section: Bile Composition Goalmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, miR-122-5p is the most abundant liver-derived miRNA, constituting 70% of the total miRNA in the liver (14), and thus, a significant increase in this miRNA could be associated with hepatocyte damage, toxicity, or viral infection (15). Schmuck et al also demonstrated that the levels of miR-122-5p, miR-133a, miR-148a-3p, and miR-194 are significantly higher in the bile of liver recipients who develop AR within the first 6 months after transplantation and during the AR episode (16). Recently, Shaked et al, by using the framework of the Immune Tolerance Network Immunosuppression Withdrawal (ITN030ST) and Clinical Trials in Organ Transplantation (CTOT-03) studies, identified in plasma two miRNAs (miR-483-3p and miR-885-5p) that, when combined together in a signature, could diagnose and predict liver rejection with high accuracy [area under the curve (AUC) = 89.5%; 95% CI = 82–96%; sensitivity = 83.8%; specificity = 87.1%; positive predictive value (PPV) = 72% and negative predictive value (NPV) = 93%] (7).…”
Section: Introductionmentioning
confidence: 99%
“…The early diagnosis of acute renal rejection is important for effective treatment with immunosuppressants and corticosteroids. Increasing evidence has demonstrated that miRNAs are differentially expressed in acute renal rejection and serve essential roles in its progression ( 34 36 ). Previous studies have reported that miRNAs may be used as a liquid biopsy tool, for applications including distinguishing squamous cell carcinoma in lung cancer biopsies ( 37 ), and predicting the pathological response ( 38 ) of patients with and without acute rejection ( 39 , 40 ).…”
Section: Discussionmentioning
confidence: 99%